2016
DOI: 10.3389/fnins.2016.00358
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Role of Sialylation in Prion Diseases

Abstract: Mammalian prion or PrPSc is a proteinaceous infectious agent that consists of a misfolded, self-replicating state of a sialoglycoprotein called the prion protein, or PrPC. Sialylation of the prion protein N-linked glycans was discovered more than 30 years ago, yet the role of sialylation in prion pathogenesis remains poorly understood. Recent years have witnessed extraordinary growth in interest in sialylation and established a critical role for sialic acids in host invasion and host-pathogen interactions. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 161 publications
(247 reference statements)
7
74
0
Order By: Relevance
“…In summary, the current study supports the new hypothesis that sialylation of PrP Sc controls its fate in an organism (27).…”
Section: Figure 4 Analysis Of Prpsupporting
confidence: 74%
See 1 more Smart Citation
“…In summary, the current study supports the new hypothesis that sialylation of PrP Sc controls its fate in an organism (27).…”
Section: Figure 4 Analysis Of Prpsupporting
confidence: 74%
“…Glycoproteins or glycolipids that lack sialic acids at terminal positions serve as a "pathogen-associated molecular pattern" used by mammalian immune systems to recognize pathogens or asialoglycoproteins that need to be removed (25). Bearing in mind that sialylation serves as a molecular marker of self versus nonself, we proposed a hypothesis that sialylation determines the fate of prions in an organism (27) …”
mentioning
confidence: 99%
“…Previously, we proposed that sialylation of PrP Sc glycans prevents the innate immune system and microglia from recognition of prions as potential pathogens and that sialylation controls PrP Sc fate in an organism [18][19][20][21]. In support of this hypothesis, we showed that PrP Sc with reduced sialylation levels does not induce prion disease in wild-type animals when administered via intracranial or intraperitoneal injections [19][20][21].…”
Section: Introductionsupporting
confidence: 62%
“…Baskakov and colleagues convincingly demonstrated that sialylation status differs among prion strains (27,29), which could dictate fH binding. Katorcha et al reported that PrP Sc sialylation increased prion infectivity (28).…”
Section: Discussionmentioning
confidence: 99%
“…fH may bind sialylated PrP Sc and facilitate disease via the shuttling mechanism described above. Hepatocarcinoma cells utilize sialic acids to selectively adhere to secondary lymphoid organs (reviewed in 29). Perhaps fH aids sialylated prions infect lymphoid organs via a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%